2018
DOI: 10.2166/wpt.2018.085
|View full text |Cite
|
Sign up to set email alerts
|

Support tools to predict the critical structural condition of uninspected pipes for case studies of Germany and Colombia

Abstract: Several deterioration models have been used to predict the structural condition of sewer pipes, and some have been applied in different cities in the world. However, each one of these models has not been proved simultaneously for case studies with different characteristics (topographic conditions, soil uses, demographic growth, utilities' service operation and city's dynamic) and the use of their predictions have not been analyzed to support different management objectives. Therefore, the objective of this wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…(2) Scenario 2: the age together with other sewer available characteristics such as the material, the type of effluent (sewerage), the pipe's depth, length, slope and diameter as input independent variables that could influence the structural condition of the sewer assets (Ariaratnam et al, 2001;Baik et al, 2006;Younis and Knight, 2010;Tscheikner-Gratl et al, 2016;Hern andez et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…(2) Scenario 2: the age together with other sewer available characteristics such as the material, the type of effluent (sewerage), the pipe's depth, length, slope and diameter as input independent variables that could influence the structural condition of the sewer assets (Ariaratnam et al, 2001;Baik et al, 2006;Younis and Knight, 2010;Tscheikner-Gratl et al, 2016;Hern andez et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…In the search for efficient models and tools to predict the physical condition of underground sewer infrastructure, studies such as Sousa, Matos, and Matias (2014), Jiang, Keller, Bond, and Yuan (2016), Santos et al (2017), Caradot et al (2018), andHernández, Caradot, Sonnenberg, Rouault, and were aimed to compare a collection of different models, and identifying the ones that produced the best results under several conditions. Additionally, Laakso, Kokkonen, Mellin, and Vahala (2018) and Elmasry, Hawari, and Zayed (2017) coupled different models as a part of a single framework with the idea of combining the predictive capabilities of such models in a single tool.…”
Section: Predictive Modelsmentioning
confidence: 99%
“…These models were used to predict three levels of sewer condition: good, medium, and bad. Hernández et al (2018) evaluated two different models' predictive outcomes, namely, LR and RF, for two different case studies, a city in Europe and a city in South America. The models were used to predict the critical structural condition of sewer pipes in both cities on a four-level scale.…”
Section: Predictive Modelsmentioning
confidence: 99%
“…Few studies evaluated the performance of deterioration models to simulate the condition distribution of the network (Caradot et al 2017(Caradot et al , 2018Duchesne et al 2013;Hernández et al 2018;Ugarelli et al 2013). They indicated that survival analysis and Markov models outperform a simple random model for predicting the condition distribution of the network, especially in the case of low data availability.…”
Section: Modelling Of Sewer Structural Deteriorationmentioning
confidence: 99%
“…Main machine learning methods used as deterioration models are Random Forest (e.g. Harvey and McBean 2014; Laakso et al 2018; Rokstad and Ugarelli 2015), Support Vector Machines (e.g Hernández et al 2018;Mashford et al 2011;Sousa, Matos, and Matias 2014),. and Neural Networks (e.g Jiang et al 2016;Sousa, Matos, and Matias 2014;Tran, Ng, and Perera 2007)…”
mentioning
confidence: 99%